Removal of boron and arsenic by forward osmosis membrane : influence of membrane orientation and organic fouling - Jin, Xue (2013)
The potential application of forward osmosis (FO) membranes in water treatment and desalination requires an improved understanding of the factors that govern the rejection of trace contaminants. This study investigated the influence of membrane orientation and organic fouling on the performance of FO membrane in removing boron and arsenic. Results of laboratory-scale crossflow membrane filtration experiments showed that the inorganic contaminants were rejected at a much lower rate when membrane active layer was facing draw solution (AL-DS) compared to the active layer-facing feed water (AL-FW) orientation, as a result of the more severe concentrative internal concentration polarization (ICP) in the latter orientation. The difference in boron rejection between the two membrane orientations was greater due to its higher permeability through the FO membrane. In the AL-FW orientation, the formation of an alginate fouling layer on the membrane surface could enhance the sieving effect and thus improve the rejection of arsenious acid with relatively larger molecular size. In the AL-DS orientation, alginate fouling in the membrane support layer had adverse effect on boron rejection at water flux below 4.2 μm/s (15.3 L/m2/h), attributed to the foulant enhanced concentrative ICP effect. Findings have important implications in the performance and applicability of FO membrane processes.